2010
DOI: 10.1099/vir.0.022301-0
|View full text |Cite
|
Sign up to set email alerts
|

Murine cytomegalovirus major immediate-early protein 3 interacts with cellular and viral proteins in viral DNA replication compartments and is important for early gene activation

Abstract: Murine cytomegalovirus (MCMV) immediate-early protein 3 (IE3) is essential for successful viral infection. This study developed MCMVs with an EGFP-fused IE3 gene in order to study IE3 gene expression, subnuclear distribution and biological function, as well as to examine the interaction of IE3 with cellular and viral proteins. The generated viruses included MCMVIE3gfp, in which IE1 was completely removed by the in-frame fusion of exons 3 and 5 and the C terminus of IE3 was tagged with EGFP, and MCMVIE1/3gfp, i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
44
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(49 citation statements)
references
References 47 publications
3
44
0
Order By: Relevance
“…Our data could have considerable implications for several studies assigning defined MCMV phenotypes and functions to pIE3 (11,(26)(27)(28), e.g., the analysis of cell cycle regulation. Although wt MCMV infection results in G 1 and G 2 arrest and the ⌬ie3 virus has lost this ability, ectopically expressed pIE611 exhibits cell cycle arrest activity only in G 1 and not G 2 (29), exemplifying the occasion for reevaluation.…”
Section: Discussionmentioning
confidence: 99%
“…Our data could have considerable implications for several studies assigning defined MCMV phenotypes and functions to pIE3 (11,(26)(27)(28), e.g., the analysis of cell cycle regulation. Although wt MCMV infection results in G 1 and G 2 arrest and the ⌬ie3 virus has lost this ability, ectopically expressed pIE611 exhibits cell cycle arrest activity only in G 1 and not G 2 (29), exemplifying the occasion for reevaluation.…”
Section: Discussionmentioning
confidence: 99%
“…IE-3 is the MCMV functional homologue of HCMV IE-2, which is the major transactivator of early gene expression (Angulo et al, 2000;Keil et al, 1987aKeil et al, , 1987bMartínez et al, 2010;Messerle et al, 1992). We previously showed that allogeneic transplantation induced reactivation of IE gene expression 48 h after transplant, and that RNA polymerase phosphorylated at Ser2 (Pol II pS2) was recruited to both the MIEP and the IE-3 coding region (Hummel et al, 2001;Liu et al, 2013).…”
Section: Nf-k B and Ap-1 Family Members Are Differentially Regulated mentioning
confidence: 99%
“…Plasmid pBB5.5, containing the whole M112-113 gene and promoter, was generously provided by M. Messerle (5,7,8); pET (expressing GFP) and pgfie3 (expressing GFPtagged IE3) were reported previously (6). A diagram of part of the M112-113 gene and the constructed M112-113-expressing vectors are shown in Fig.…”
Section: Methodsmentioning
confidence: 99%
“…M112-113 proteins are detectable at almost the same time as IE3, but M112-113 gene expression is upregulated strongly by IE3 (6). Compared to HCMV genes, M112-113 is the equivalent of HCMV UL112-113, and MCMV IE3 is the counterpart to HCMV IE2 (9).…”
mentioning
confidence: 96%
See 1 more Smart Citation